Comparison of encrypted control approaches and tutorial on dynamic systems using Learning With Errors-based homomorphic encryption. (2022) - Kim, Junsoo; Kim, Dongwoo; Song, Yongsoo; Shim, Hyungbo; Sandberg, Henrik; Johansson, Karl H.
Abstract: Encrypted control has been introduced to protect controller data by encryption at the stage of computation and communication, by performing the computation directly on encrypted data. In this article, we first review and categorize recent relevant studies on encrypted control. Approaches based on homomorphic encryption, multi-party computation, and secret sharing are introduced, compared, and then discussed with respect to computational complexity, communication load, enabled operations, security, and research directions. We proceed to discuss a current challenge in the application of homomorphic encryption to dynamic systems, where arithmetic operations other than integer addition and multiplication are limited. We also introduce a Learning With Errors based homomorphic cryptosystem called "Gentry-Sahai-Waters" scheme and discuss its benefits that allow for recursive multiplication of encrypted dynamic systems, without use of computationally expensive bootstrapping techniques.